AGE ESTIMATION OF THIRD MOLAR IN SOUTH INDIAN POPULATION BY ABFO RECOMMENDED MINCER METHOD – AN INDIAN SPECIFIC FORMULA (Journal of Forensic Medicine & Toxicology, 2020)
In overview stage G, maxillary right and left third molar with mandibular right third molars are considerable variability in age prediction. It was concluded that the eight stage system was less prone to examiner error. Finally, we believe that, based on our results, and the differences between them and those of other populations, where in agreement with mincer et al. present study shows better accuracy. Nevertheless, this remains as an yet to be proven concept since there is no indication at all regarding the use of country-specific information influencing the percentage of correctly identified subject.
Keywords: Orthopantomogram; Mincer method; Demirjian method; dental age estimation; forensic odontology; radiographic age estimation; third molar age estimation